2009
DOI: 10.1186/1471-2229-9-63
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a rice mutator-phenotype derived from an incompatible cross-pollination reveals transgenerational mobilization of multiple transposable elements and extensive epigenetic instability

Abstract: Background: Inter-specific hybridization occurs frequently in plants, which may induce genetic and epigenetic instabilities in the resultant hybrids, allopolyploids and introgressants. It remains unclear however whether pollination by alien pollens of an incompatible species may impose a "biological stress" even in the absence of genome-merger or genetic introgression, whereby genetic and/or epigenetic instability of the maternal recipient genome might be provoked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…[36][37][38] For example, incompatible cross-pollination promotes the transgenerational mobilization of transposons that promote epigenetic instability. 39 This has led to the proposal that genetics drives epigenetics. 40 Although a genetic focus is predominant in the current concepts of biology, it will be an integration of epigenetics and genetics, with neither being dominant, that likely will provide a more accurate perspective on the molecular control of biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] For example, incompatible cross-pollination promotes the transgenerational mobilization of transposons that promote epigenetic instability. 39 This has led to the proposal that genetics drives epigenetics. 40 Although a genetic focus is predominant in the current concepts of biology, it will be an integration of epigenetics and genetics, with neither being dominant, that likely will provide a more accurate perspective on the molecular control of biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have identified transpositional activation or mobilization of several TEs in the rice- Zizania introgression lines including RZ35 [30,33,34]. To further investigate if mobilization of additional TEs or mobilization sites of previously identified TEs in the RZ35 genome, we applied a PEM detection strategy (Figure S1) as employed previously by Sabot et al [42].…”
Section: Methodsmentioning
confidence: 99%
“…Apart from bona fide hybridization, the germinating alien pollens may constitute a "biological stress" to the recipient stigma genome due to its mechanistic resemblance to pathogen attack wherein the foreign DNA usually does not integrate into the host genome, yet its interaction with the host could provoke genetic and epigenetic instabilities of the host genome [27-30]. Therefore, in contrast to the hybridization and polyploidy, alien pollen-induced variations may represent an underlying mechanism that can also contribute to plant genome evolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, some mutator-phenotype might derive from an incompatible cross-pollination and selfing instead of compatibility. It was reported that transgenerational epigenetic instability in the form of altered cytosine methylation and its associated TE activity occurred in a rice mutator-phenotype produced by pollinating the rice stigma with pollen grains of Oenothera biennis (Wang et al 2009). Whether the hybrids contain genomeic material of the paternal hybrid or not, need to be analyzed by genomic in situ hybridization (GISH).…”
Section: Discussionmentioning
confidence: 99%